Absence of Pear1 does not affect murine platelet function in vivo. Issue 146 (October 2016) - Criel, Maarten; Izzi, Benedetta; Vandenbriele, Christophe; Liesenborghs, Laurens; Van kerckhoven, Soetkin; Lox, Marleen; Cludts, Katrien; Jones, Elizabeth A.V.; Vanassche, Thomas; Verhamme, Peter; Hoylaerts, Marc
Abstract: Background: Platelet Endothelial Aggregation Receptor-1 (PEAR1) is a transmembrane platelet receptor that amplifies the activation of the platelet fibrinogen receptor (αIIbβ3) during platelet aggregation. In man, Pear1 polymorphisms are associated with changes in platelet aggregability. In this report, we characterized Pear1 expression and function in murine platelets. Methods: Pear1 phosphorylation and signaling, platelet aggregation, α-degranulation and clot retraction were studied in WT and Pear1 −/− platelets. The function of Pear1 in haemostasis and thrombosis was studied in a mouse tail vein bleeding and ferric chloride-induced mesenteric thrombosis model. Results: Mature murine platelets express Pear1 on their membrane and clustering of Pear1 by anti-Pear1 antibodies triggered platelet aggregation. Pear1 was weakly phosphorylated during collagen-induced murine platelet aggregation and was translocated to the cytoskeleton. Absence of murine Pear1 impaired dextran sulfate-induced platelet aggregation, but did not impact collagen-, AYPGK and ADP-induced platelet aggregation, coupled to a lower Pear1 expression in murine than in human platelets and to weaker Pear1-mediated downstream signaling. Neither clot retraction nor α-degranulation was affected in Pear1 −/− mice. Likewise, in vivo tests like the tail vein bleeding time and thrombus formation in mesenteric veins were similar in WT and Pear1 −/− mice. Conclusion: Murine platelet Pear1 shares a number of characteristics with human platelet PEAR1. Nevertheless, murine Pear1 contributes less to platelet function as does human PEAR1 and does not overtly impact haemostasis and thrombosis in mice. Highlights: Murine Pear1 is primarily expressed on the platelet membrane. Platelet Pear1 is phosphorylated during murine platelet aggregation. Clustering of murine Pear1 triggers platelet aggregation. Pear1 does not contribute to murine haemostasis or thrombosis.